Formulasi Sediaan Lipstik Ekstrak Air Buah Syzygium cumini Dalam Bentuk Liquid - Sari, Dwi Augusnita; Darsono, Farida Lanawati; Wijaya, Sumi (Jurnal Farmasi Sains dan Terapan, 2017)
Now-a-days decorative cosmetics are essential needs for women especially lipstick. Lipstick is one of the cosmetics products which is used to increasing the aesthetic of facial make-up. A local tradable fruit called Syzygium cumini can be used as an alternative in conventional lipstick. Syzygium cumini anthocyanin-rich fruit contain 892 mg anthocyanins per 100g of fresh fruit. The purpose of this research was to find out the increasing of difference (HPMC) in liquid lipstick and to find out influence of the best formulation based on physical test, effectiveness test, safety test and acceptability test. Lipstick in liquid form was chosen because it has advantages such as can be easy to attached, easy to apply and easy to dry so that the formulation required a thickening agent that has properties to fulfill the characteristics of liquid lipstick. HPMC is a thickening agent and can help improve the viscosity of formulation liquid lipstick. The concentration of Syzygium cumini fruit extract was used 20% formulated using HPMC at a concentration of 0.75%; 1% and 2%. The results showed that the increasing concentration of HPMC significantly affect on pH test, viscosity, adhesion, and drying time; the decreasing of spreadness and the smearness of liquid lipstick. The best formula was the formula contained HPMC 2%, based on physical test (viscosity, homogeneity), effectiveness test (smearness, spreadness, stickiness, drying time), safety test and acceptability test.